The response of skin friction, wall heat transfer and pressure drop to wall waviness in the presence of buoyancy. (1982) - Rao, C. N. B.; Sastri, K. S.
Abstract : Laminar natural convection flow and heat transfer of a viscous incompressible fluid confined between two long vertical wavy walls has been analysed taking the fluid properties constant and variable. In particular, attention is restricted to estimate the effects of viscous dissipation and wall waviness on the flow and heat transfer characteristics. Use has been made of a linearization technique to simplify the governing equations and of Galerkin's method in the solution. The solutions obtained for the velocity and the temperature-fields hold good for all values of the Grashof number and wave number of the wavy walls.